2012
DOI: 10.4172/2329-6771.1000103
|View full text |Cite
|
Sign up to set email alerts
|

Current Exercise Behaviors Of Breast Cancer Patients Diagnosed With Chemotherapy-induced Peripheral Neuropathy

Abstract: Introduction: Chemotherapy-induced peripheral neuropathy (CIPN) is a common, dose-limiting effect of cancer therapy. The neuropathic pain associated with CIPN often has negative implications on an individual's quality of life (QOL) and has long been recognized as one of the more difficult types of pain to treat. Treatment of neuropathic pain due to CIPN often requires a multidisciplinary approach, with much attention focused on the use of pharmacological therapies. However, in most instances, these agents have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Only 15% of patients surveyed were currently meeting the recommended levels of physical activity. Yet, these physically active patients reported a significantly higher quality of life (QOL) and experienced less pain than their sedentary counterparts [13], lending some credibility to the hypothesis that an exercise intervention would be beneficial in attenuating symptoms of CIPN and improving the overall QOL of cancer patients. However, it was unknown if the sedentary patients refrained from exercise because of the symptoms of CIPN or some other factor.…”
Section: Introductionmentioning
confidence: 99%
“…Only 15% of patients surveyed were currently meeting the recommended levels of physical activity. Yet, these physically active patients reported a significantly higher quality of life (QOL) and experienced less pain than their sedentary counterparts [13], lending some credibility to the hypothesis that an exercise intervention would be beneficial in attenuating symptoms of CIPN and improving the overall QOL of cancer patients. However, it was unknown if the sedentary patients refrained from exercise because of the symptoms of CIPN or some other factor.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance and aerobic exercise are associated with improvements in nerve conduction velocity 21 , 22 and increased axon regeneration. 23 Long-term exercise has also been shown to induce changes in both the vasculature and metabolic systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical trials examining the role of exercise in preserving neurological function following chemotherapy are limited. One recent investigation on the current exercise behaviors of breast cancer patients diagnosed with CIPN patients reported that those individuals who met the amount of recommended physical activity levels reported a significantly higher quality of life and experienced significantly less pain than their sedentary counterparts [56]. A follow-up investigation examined the effect of 12 weeks of supervised exercise training on symptoms of CIPN and found that exercise training positively impacted neurological function.…”
Section: Exercise Rehabilitationmentioning
confidence: 99%